Review on metal contamination in equatorial estuaries in the Brazilian Northeast - Santos, Thays Thayanne Luz; Marins, Rozane Valente; Alves, Letícia Paulino (Frontiers in Earth Science, 2023)
The present study provides an overview and assessment of the metals and trace metals registered in water, sediment, and biota in estuaries of the Equatorial Zone of the Brazilian Northeast (EZBN). The study aims to compare the degree of contamination and highlight necessary complementary research. The EZBN is characterized by the transition between the humid and hot Amazonian climate and the hot and dry semiarid climate. The spatial distribution identified enrichment for Cu, Pb, Zn, Hg, and Fe in the sediment, and sequential extraction of metals suggested low to medium mobility of metals along the environments. The Parnaíba River Delta, Curimataú, and the Anil and Bacanga estuaries were the environments with the lowest sediment quality for Pb, Zn, Cu, and Fe, identified by the geoaccumulation index (Igeo). The deposits in these estuaries were related to anthropogenic contributions from domestic sewage and inadequate disposal of wastewater from shrimp farms. However, more studies to determine the natural background levels based on sediment cores and metal speciation are necessary to better differentiate between natural and anthropic sources. Oysters, carnivorous fishes, and crustaceans had the best feedback as biomonitors for Cu, Pb, Zn, and Hg, but the application of biomonitoring needs to be expanded and maintained so that the potential for environmental degradation, which can have significant consequences both for the ecosystem and for human health, can be closely monitored in the EZBN estuaries.